Intracapillary glomerular metastases in a nephrectomy specimen removed for ipsilateral renal cell carcinoma. Issue 6 (June 1994) - Carr, R A; Yoong, A K; Newman, J
Abstract : A case of intraglomerular metastases observed in a nephrectomy specimen removed for primary renal cell carcinoma is reported. The intraglomerular metastases arose by dissemination of malignant cells into the systemic circulation via invasion of the renal veins. Intraglomerular metastases are therefore an indicator of malignant dissemination which in turn should be associated with a poor prognosis. It is recommended that in nephrectomies undertaken for primary renal cell carcinoma at least one random block of renal cortex should be examined to confirm or exclude intraglomerular metastases.